Answer:
The zeros are 0 ,2, and 1
Explanation:
f (x) = 2x (x - 2) (1 - x)
set f(x) equal to y
y = 2x (x - 2) (1 - x)
solve when y is 0 because when y is 0 then it is an x-intercept
0 = 2x (x - 2) (1 - x)
separate all of the equations out
0 = 2x
0 = (x - 2)
0 = (1 - x)
solve for x for each equation
0 = 2x
- divide both sides by 2
- 0/2 = 0 and 2x/2 = x
- 0 = x
- x = 0
0 = (x - 2)
- add 2 to both sides
- 0 + 2 = 2 and (x - 2) + 2 = x
- 2 = x
- x = 2
0 = (1 - x)
- subtract 1 from both sides
- 0 - 1 = -1 and (1 - x) - 1 = -x
- -1 = - x
- multiply both sides by -1
- -1 · -1 = 1 and -x · -1 = x
- 1 = x
- x = 1